From Brazil to The Planet: politics of race in the american black press (PerCursos, 2024)
In the passage of the nineteenth to the twentieth century, Brazilian and American Black intellectuals expressed their views on racial disputes over the Black press. This article evaluates views of Black politics in the U.S. and Brazil as an essential grounding of the struggle for civil rights, understanding the past of both countries as emerging from a collective experience of discrimination. The primary sources are the letters written by J. S. Moore, an African American intellectual who lived in Bahia, Brazil. Moore addressed his writings to newspapers such as the New York Amsterdam News, Chicago Defender, and particularly the Richmond Planet. His critics' articles debated directly with editors from 1917 to the 1930s. The dialogue between the American continents also sheds light on Brazilians’ racial issues. It gives us a more complex perspective of the global fight against racism and makes it possible to understand the potential choices for resistance among diasporic societies.
Keywords: black press; United States of America; Brazil; black activism; pan-africanism